Expanding the knowledge of Ruddy Shelduck (Tadorna ferruginea Pallas, 1764) distribution in Serbia: New findings and implications for conservation - Nikolić Marko Lj.; Medenica Ivan J. (Kragujevac Journal of Science)
The Ruddy Shelduck (Tadorna ferruginea) is a vagrant passage and wintering species whose presence and distribution in Serbia have been inadequately studied. This study presents new findings of T. ferruginea in Serbia based on two sources of data: unpublished eBird checklists from 2014 to 2019 and new data collected from 2020 to 2023. Observations were conducted at various localities across Serbia, including Jezero Ćelije, Begečka Jama, Smilovci Lake, Aleksandrovačko Lake, Sava shipyard, fish farms of Novi Kneževac, Bečej, and Čenta, as well as the Special Nature Reserve Slano Kopovo. These sightings contribute to our understanding of the species' distribution within Serbia and underscore the importance of ongoing monitoring efforts. The potential impacts of these results on upcoming research and conservation initiatives, which are focused on safeguarding the populations of T. ferruginea within the area, are examined.